Single-phase power shunt active filter design using photovoltaic as reactive power compensator - Dwinanto, B.; Setiyono, Setiyono; Thalib, F.; Siswono, H. (Electronics and electromechanics, 2025)
Introduction. The rapid production of electronic equipment circulating and used by the public has resulted in a decline in the power quality in the power system. The goal of the article is to build a parallel active filter for reactive power compensation in a single-phase power system using photovoltaic (PV) as the input DC link voltage for the inverter through simulation modeling using MATLAB/Simulink. Methods. The method used is to design a parallel active filter modeling for a single-phase electrical network that serves loads in the form of AC DC converters with inductive recessive and capacitive recessive loads using MATLAB/Simulink. Results. The simulation results show that the total harmonic distortion (THD) value of the system before being screened is 37.93 % for inductive resistive loads and 18.77 % for capacitive resistive loads, and after going through screening the THD value can drop significantly by 0.35 % for inductive resistive loads and 1.45 % for resistive capacitive loads. Practical value. PV systems can be used as power generators to provide a voltage of 800 V on a single-phase parallel active power filter using a voltage source inverter. References 30, table 2, figures 11.